Applying mass spectrometry-based qualitative proteomics to human amygdaloid complex - Fernández-Irigoyen, Joaquín; Zelaya, María V.; Santamaría, Enrique (Frontiers in Cellular Neuroscience, 2014)
The amygdaloid complex is a key brain structure involved in the expression of behaviours and emotions such as learning, fear, and anxiety. Brain diseases including depression, epilepsy, autism, schizophrenia, and Alzheimer`s disease, have been associated with amygdala dysfunction. For several decades, neuroanatomical, neurophysiological, volumetric, and cognitive approaches have been the gold standard techniques employed to characterize the amygdala functionality. However, little attention has been focused specifically on the molecular composition of the human amygdala from the perspective of proteomics. We have performed a global proteome analysis employing protein and peptide fractionation methods followed by nano-liquid chromatography tandem mass spectrometry (nanoLC-MS/MS), detecting expression of at least 1820 protein species in human amygdala, corresponding to 1814 proteins which represent a 9-fold increase in proteome coverage with respect to previous proteomic profiling of the rat amygdala. Gene ontology analysis were used to determine biological process represented in human amygdala highlighting molecule transport, nucleotide binding, and oxidoreductase and GTPase activities. Bioinformatic analyses have revealed that nearly 4% of identified proteins have been previously associated to neurodegenerative syndromes, and 26% of amygdaloid proteins were also found to be present in cerebrospinal fluid (CSF). In particular, a subset of amygdaloid proteins was mainly involved in axon guidance, synaptic vesicle release, L1CAM interactome, and signaling pathways transduced by NGF and NCAM1. Taken together, our data contributes to the repertoire of the human brain proteome, serving as a reference library to provide basic information for understanding the neurobiology of the human amygdala.